2008
DOI: 10.1016/j.fgb.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of LaeA for secondary metabolism and sclerotial production in Aspergillus flavus

Abstract: The nuclear regulator LaeA has been shown to govern production of multiple secondary metabolites in A. nidulans and A. fumigatus. Herein we examine the role of this protein in Aspergillus flavus. Similarly as in other Aspergilli, LaeA had a major effect on A. flavus secondary metabolism where ΔlaeA and over-expression laeA (OE::laeA) strains yielded opposite phenotypes resulting in decreased (increased) secondary metabolite production. The two mutant strains also exhibited striking morphological phenotypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
181
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 37 publications
15
181
0
Order By: Relevance
“…For our studies on gliotoxin, June Kwon-Chung (NIAID, Bethesda, Maryland, USA) provided A. fumigatus strains B-5233 (WT), ΔgliP, and gliPR (77). Additionally, Nancy Keller (University of Wisconsin, Madison, Wisconsin, USA) provided the A. fumigatus strains Af293 (WT), ΔgliZ, gliZR, ΔlaeA, laeA-R, as well as the Aspergillus flavus strains A. flavus NRRL3357 (WT), ΔlaeA, and laeA-R (78,79). For ROS scavenging studies, we used A. fumigatus strains G10 (WT), ΔcatA, and Δcat1/2, and Ku80 (WT), Δsod1/2/3, and Dal (WT), Δyap1 (36)(37)(38).…”
Section: Methodsmentioning
confidence: 99%
“…For our studies on gliotoxin, June Kwon-Chung (NIAID, Bethesda, Maryland, USA) provided A. fumigatus strains B-5233 (WT), ΔgliP, and gliPR (77). Additionally, Nancy Keller (University of Wisconsin, Madison, Wisconsin, USA) provided the A. fumigatus strains Af293 (WT), ΔgliZ, gliZR, ΔlaeA, laeA-R, as well as the Aspergillus flavus strains A. flavus NRRL3357 (WT), ΔlaeA, and laeA-R (78,79). For ROS scavenging studies, we used A. fumigatus strains G10 (WT), ΔcatA, and Δcat1/2, and Ku80 (WT), Δsod1/2/3, and Dal (WT), Δyap1 (36)(37)(38).…”
Section: Methodsmentioning
confidence: 99%
“…4) According to another study, KA production was lost in the laeA disruption (ÁLaeA) strain in A. flavus, 5) but it was uncertain how LaeA controlled KA production. To elucidate laeA regulation of KA production in A. oryzae, we produced a disruption mutant.…”
mentioning
confidence: 99%
“…Another gene, laeA, has also been shown to regulate expression of biosynthetic gene clusters in species of Aspergillus (Bok & Keller, 2004;Keller et al, 2005;Fox & Howlett, 2008). In addition, it has been shown that laeA negatively affects the regulation of veA (Kale et al, 2008). The loss of laeA results in gene silencing (Bok et al, 2006b;Perrin et al, 2007).…”
Section: Environmental Cues Affecting Secondary Metabolite Productionmentioning
confidence: 99%